RETRACTED: Clinico-demographic and survival profile of people living with HIV on antiretroviral treatment - Shaik, Riyaz Ahamed; Holyachi, Sharan K.; Ahmad, Mohammad S.; Miraj, Mohammed; Alzahrani, Mansour; Ahmad, Ritu Kumar; Almehmadi, Bader A.; Aljulifi, Mohammed Zaid; Alzahrani, Meshari A.; Alharbi, Mashael B.; Ahmed, Mohammed Muzammil (Frontiers in Public Health, 2023)
Objective: To assess the sociodemographic profile and survival profile of HIV pa-tients. Methods: A retrospective cohort study was conducted among patients enrolled at a sin-gle antiretroviral therapy center in North Karnataka. A total of 11099 were recruited from April 2007 to January 2020. The outcome of interest was the time to death in months of HIV patients on ART. R Studio Version 1.3.1093 was used for statistical analysis. Results: Out of 7423 HIV-positive people majority were female (51.4%), heterosexual typology (89.2%), and in the age group 31 to 45 years (45.5%). In the multivariable analysis the hazards of mortality increased by 3.11 times and 2.11 times in patients with baseline CD4 count <=50 and baseline CD4 count 51 to 200 respectively as compared to those who had baseline CD4 count >200. The mortality rate was high in the initial three months after the start of ART and overall survival probabilities among people with HIV declined over follow-up time. Conclusion: This study proved that age, sex, baseline CD4 count, and TB status act as risk factors for mortality among people with HIV. Prevention strategies, control measures, and program planning should be done based on the sociodemographic deter-minants of mortality. Keywords: HIV; CD4 counts; Tuberculosis; risk factors; ART, Retroviral agents